A Jesuit in the Forbidden City Matteo Ricci 1552-1610 - Hsia, R. Po-chia, 1953- (Oxford University Press, 2010)
The remarkable life of the Italian Jesuit Matteo Ricci, one of the most famous missionaries of all time and the founder of the Catholic Mission in China. This is the first critical biography to use all relevant sources, not only in western languages but in Chinese as well.